2016
DOI: 10.4103/0973-029x.190912
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear fractal dimension: A new objective approach for discriminating normal mucosa, dysplasia and carcinoma

Abstract: Background:Various clinical and histological factors have helped in predicting the survival of patients with oral squamous cell carcinoma (OSCC). However, there has been a need for more specialized diagnostic and prognostic factors to avoid subjective variation among opinion. Thus, fractal dimension (FD) can be used as an index of the morphological changes that the epithelial cells undergo during their transformation into neoplastic cell. In oral cancer study, nuclear FD (NFD) can be used as a quantitative ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Fractal dimension (FD), which quantifies a pattern’s complexity by comparing how detail changes with the scale at which it is measured, presents a promising method to objectively distinguish dysplasia and carcinoma from normal mucosa 206 . FD, a quantitative result of fractal analysis applied to radiological perfusion imaging, represents chaos in the perfusion pattern and can be related to the structure of the underlying vascular tree 207 209 .…”
Section: Assessment Of Head and Neck Squamous Cell Carcinoma Marginsmentioning
confidence: 99%
“…Fractal dimension (FD), which quantifies a pattern’s complexity by comparing how detail changes with the scale at which it is measured, presents a promising method to objectively distinguish dysplasia and carcinoma from normal mucosa 206 . FD, a quantitative result of fractal analysis applied to radiological perfusion imaging, represents chaos in the perfusion pattern and can be related to the structure of the underlying vascular tree 207 209 .…”
Section: Assessment Of Head and Neck Squamous Cell Carcinoma Marginsmentioning
confidence: 99%
“…The 27 eligible studies were published over 30 years (1993-2022) from different countries of origin. Forty-four percent of them were published by Indian research groups [20][21][22][23][24][25][26][27][28][29][30][31], followed by, per number, four works from Greece [32][33][34][35], three from Italy [36][37][38], and the remaining papers from different countries, such as the UK [39], Romania [40], Germany [41], Canada [42], Taiwan [43], China [44], Poland [45], and Spain [46]. All the main characteristics of the studies are reported in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…nFD seemed a reliable diagnostic tool that need standardization to be validated, but the data collected suggest the possible use of FD also as a prognostic factor. 17 Phulari, (2016), India [24] To compare the morphometric complexity using nFD in normal, epithelial dysplasia, and OC cases and to verify the differences among the various histological grades of dysplasia and OC Histological specimens for assessment for distinguishing OC and various degrees of dysplasia…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations